Analisa Kinerja Nilai Pajak Tertagih Pada Pajak Bumi dan Bangunan Studi Kasus di Kabupaten Bengkalis - Husni Mubarak Mukhtar (Politeknik Negeri Bengkalis, 2020)
This research title is Analysis of Target Value from collected Tax on Land and Building Tax covers in the Bengkalis District. The data used is the Regional Revenue Agency (BAPENDA) for the past 5 years. The results of this study find that collected taxes for world tax and tax (PBB tax) in this region is very low, average tax collected has 44,76 percent in 5 years. it has 47,36 percent or it same with Rp.8.294.757.277 from Rp.17.514.731.453 in total PBB tax 2019. The research finds 2 sub-districts (Bukit Batu & Rupat Utara) called success to collect PBB tax more than 80 percent, 3 sub-districts (Bantan, Siak Kecil & Rupat) are called middle level with 55-75 percent, and they are haves less collect PPB value than 50 percent of 6 sub-districts (Bengkalis, Mandau, Pinggir, Bathin Solapan, Bandar Laksmana & Talang Mandau).